Antibacterial and biofilm inhibition activities of Melastoma malabathricum stem bark extract against Streptococcus mutans - Rohazila Mohamad Hanafiah; Wan Syaidatul Aqma; Wan Ahmad Yaacob; Zulfahmi Said; Nazlina Ibrahim (Universiti Sains Malaysia, 2024)
Indexed by Scopus